Footprints of drought risk on Africa’s agricultural, water and nutritional security - Sharma, Tarul; Amarnath, Giriraj; Amarasinghe, Upali; Seid, Abdulkarim (IOP Publishing, 2024)
Prolonged and recurrent droughts seriously threaten Africa’s food and water security. This threat frequently coexists with human-induced calamities, such as domestic and international conflicts and civil unrest, which could exacerbate the socio-economic instability already present in the region. Using a novel data-driven approach, we evaluated how drought risk in Africa affects the security of various crucial sectors of sustainable development, such as agriculture, water, and food nutrition/health (referred here as ‘nutritional’). Our findings show that different sectors and geographical areas exhibit distinct risk footprints. In Central African countries, for instance, we found that social instability linked to higher nutritional risk is more prevalent than that resulting from the agriculture and water sectors. Socio-economic volatility rather than uncertainty in the climate is the primary driver of this elevated nutritional risk. However, most Northern African countries are at risk of considerable agriculture and water insecurity because of extreme water stress and unstable climate trends. We indicate that the risk is majorly driven by recurrent drought events in Southern Africa, which significantly affect inclusive sectoral securities. The cause of higher risks in Eastern and Western Africa has been found to be an unfavorable interaction of all the risk components—vulnerability, exposure, and hazard. Notably, basic amenities, climate stability, and access to sustainable and renewable water sources are often missing from Africa’s sectoral risk hotspots. Our results emphasize the necessity of maximizing the efficacy of bottom-up initiatives to achieve sustainable food and water security, by integrating socio-economic policies and climate change at the granular level through observation.